Optimal collaboration in services for adolescents with neurodevelopmental disorders: professionals’ perspectives - Salminen, Jaanet; Laasanen, Miia; Leinonen, Leena; Eklöf, Anniina; Karukivi, Max; Alin, Minna; Kyttälä, Minna (Emerald Publishing, 2026)
Purpose – Collaboration is an essential component in addressing the diverse needs of children and adolescents with neurodevelopmental disorders (NDDs). However, the development of multi-sector service systems and professional collaboration face challenges due to siloed healthcare, social care and education. This study aims to examine Finnish professionals’ perspectives on optimal collaboration for adolescents with NDDs (AwNDDs).
Design/methodology/approach – Qualitative content analysis was used to examine five focus-group interviews with 25 professionals from the healthcare, social care and education sectors, all of whom work with children or AwNDDs.
Findings – The results suggest that both the service system and professional collaboration should be improved to achieve optimal collaborative service for AwNDDs. The unique aspects of professional collaboration with AwNDDs and their families were also highlighted, although to a lesser extent.
Originality/value – This study contributes to the scholarly debate on collaboration between professionals in health, social services and education, an area that has been under-researched compared to collaboration in health and social services in the context of AwNDDs. The study concludes with an interpretative summary constructed using Rose and Norwich’s (2014) model in the context of cross-sectional services and optimal collaboration for AwNDDs and their families, addressing practical issues and overarching principles for organising these services and enhancing collaboration between professionals.